Perceptions of health systems stakeholders on the factors affecting the development of family practice/family medicine in Indonesia and the strategies for improvement December 2004 - May 2005 - Agrimon, Oryzati Hilman
Background and objectives: Since initial introduction in 1982, over the last two decades the delopment of Family Practice/Family Medicine in Indonesia has not made significant acvances despite the many initiatives done. This exploratory study aimed to examine the factors affecting its development and the strategies for improvement as perceived by various health system stakeholders. Methods: A qualitative study was done, employing individual interviews and focus-group discussions (FGD) to a purposive sampling of 5 stakeholders groups covering national (Jakarta) and regional level(Yogyakarta). A total 17 policy makers, 16 health professionals, 6 health managers, 12 academicians, and 12 patients at various settings participated in the interviews; while 8 medical students, 8 community health workers and 22 housing complex residents joined 3 separate FGDs. the interviews and FGDs, guided by 2 lists of open-ended questions, were audio-taped and transcribed to facilitate content analysis. Results and discussion: various stakeholder groups idetified different perceptions regarding awareness on Family Doctor(FD)/Family Practice(FP)/Family Medicine(FM), which included misconceptions. This should be properly modified. The various stakeholders largely perceived the current status of FP/FM development in Indonesia as "on-going development", although it is still 'slow or far from expected or at initial/discussion stage'. It was affirmed with the infamiliarity of the communities/patients towards FD or FD's clinic. The factors affecting the development of FP/FM in Indonesia were identified as enablers and barriers, each covered 7 big groupings i.e: (1) FD/FP/FM concept related factors; (2)Health system related factors; (3) Political factors; (4) Educational factors; (5) Socio-cultural factors; (6) Economic factors; and (7) Environmental factors. The stakeholders identified more barriers than enablers which could explain the slow development of FP/FM. Regarding future projections of FP/FM development in Indonesia, the various stakeholders largely perceived it as good projections; however, some gave long time frame of projection. Concerning FD's roles in the evolving health system, most commonly slated roles included: "first-contact/primary care physician", "gate keeper" and "health maintenance physician". The importance of FD's roles was also underlined by most stakeholders. This showed a positive perception towards the roles of FD. Most commonly stated appropriate training for FDs in Indonesia included: CME FD training/ short course and undergraduate medical education incorporating FM curriculum. Concerning the development of Family Practice in relation with National Social Health Insurance (NSHI)/National Social Security System(NSSS)/health insurance system, the responses showed evident support of the stakeholders for the notion that "FP is based on health insurance system".